Understanding the Correlation Between Teacher and Student Behavior in the Classroom and its Consequent Academic Performance - Damasceno, Adson; Ferreira, Andressa; Gama, Thiago; Medeiros, Celso; Pereira, Elane; Oliveira, Francisco (Proceedings - Frontiers in Education Conference, 2019)
This Innovate Practice Full Paper document presents a technological ecosystem for classroom management that we call GSA. GSA is meant to be used in any class/ of any subject/k-college and supports electronically mediated in class, engaging activities learning strategies to reduce dropout rates and create more learning opportunities. In the previous study, we interviewed 123 8th and 9th-grade students and 15 teachers who had been using the GSA for two weeks. The results were promising. An increase in the level of motivation was observed. Being able to mediate in real time, teacher/student interactions create opportunities to capture valuable data that can be used to feed performance/dropout predictors. In this paper, we discuss the introduction of these predictors and how they can be used to foster preemptive measures to mitigate the problem.